Condições de existência de autoexcitação em geradores de indução conforme suas condições operativas - Mayer, Giovano (2012)
The use of alternative sources of energy requires electromechanical conversion equipments that exhibit low installation, operating and maintenance costs. In such way, small energy resources that are not connect to the power system (PS) can be benefited by the use of squirrel-cage induction generators (IG) which show such characteristics. When operating in an isolated mode, the IG is called SEIG - Self Excited Induction Generator, and in this configuration its self excitation is promoted through the connection of appropriate capacitors to the terminals of the machine stator. The existence of self-excitation in the IG depends on the value of the capacitor connected to the stator, the mechanical velocity and the load. This work aims to study the conditions of existence of self-excitation in induction generators having in mind applications in isolated generators systems. Towards this goal, initially the conditions for the existence of self-excitation are stated in terms of appropriate parameters, units and quantities, so as to highlight its relations with the operative characteristics of the machine. It is considered that the induction generator is connected to a load that contains both reactive and active components, parameterized in terms of its rated power. The self-excitation capacitors are represented by its reactive power, called self-excitation reactive power (PRAE). Self-excitation existence regions are defined which explicitate conditions for the existence and maintenance of self-excitation over, a region of operating conditions (OR) of the generator. Through the analysis of the existence of the self-excitation over the OR and the parameterization of the PRAE and the load in terms or rated power, procedures for SEIG design are established. With these procedures, the design of the SEIG is defined by the maximum load power, the worse load power factor condition, and the minimum self-excitation speed of the generator. The process of self-excitation of the generator and the design procedures are analyzed with the aid of dynamic simulations of the SEIG complete model, including the non linear model of the magnetizing inductance representing the magnetic saturation. A laboratorial bench was developed to allow studies with asynchronous generation, in particular with the SEIG. The parameters of the generator were identified experimentally and used all along the work, especially in the dynamic simulations showed. The results were also compared with experimental data collected from self-excitation tests performed with the developed laboratory bench.